Fibroglandular tissue distribution in the breast during mammography and tomosynthesis based on breast CT data: A patient‐based characterization of the breast parenchyma. Issue 3 (3rd February 2021) - Fedon, Christian; Caballo, Marco; García, Eloy; Diaz, Oliver; Boone, John M.; Dance, David R.; Sechopoulos, Ioannis
Abstract : Purpose: To develop a patient‐based breast density model by characterizing the fibroglandular tissue distribution in patient breasts during compression for mammography and digital breast tomosynthesis (DBT) imaging. Methods: In this prospective study, 88 breast images were acquired using a dedicated breast computed tomography (CT) system. The breasts in the images were classified into their three main tissue components and mechanically compressed to mimic the positioning for mammographic acquisition of the craniocaudal (CC) and mediolateral oblique (MLO) views. The resulting fibroglandular tissue distribution during these compressions was characterized by dividing the compressed breast volume into small regions, for which the median and the 25th and 75th percentile values of local fibroglandular density were obtained in the axial, coronal, and sagittal directions. The best fitting function, based on the likelihood method, for the median distribution was obtained in each direction. Results: The fibroglandular tissue tends to concentrate toward the caudal (about 15% below the midline of the breast) and anterior regions of the breast, in both the CC‐ and MLO‐view compressions. A symmetrical distribution was found in the MLO direction in the case of the CC‐view compression, while a shift of about 12% toward the lateral direction was found in the MLO‐view case. Conclusions: The location of the fibroglandular tissue in the breast under compression during mammography and DBT image acquisition is a major factor for determining the actual glandular dose imparted during these examinations. A more realistic model of the parenchyma in the compressed breast, based on patient image data, was developed. This improved model more accurately reflects the fibroglandular tissue spatial distribution that can be found in patient breasts, and therefore might aid in future studies involving radiation dose and/or cancer development risk estimation. Abstract :